Light-curve Structure and Hα Line Formation in the Tidal Disruption Event AT 2019azh - Faris, Sara; Arcavi, Iair; Makrygianni, Lydia; Hiramatsu, Daichi; Terreran, Giacomo; Farah, Joseph; Howell, D. Andrew; McCully, Curtis; Newsome, Megan; Padilla Gonzalez, Estefania; Pellegrino, Craig; Bostroem, K. Azalee; et al. (Institute of Physics Publishing, 2025)
AT 2019azh is a H+He tidal disruption event (TDE) with one of the most extensive ultraviolet and optical data sets available to date. We present our photometric and spectroscopic observations of this event starting several weeks before and out to approximately 2 yr after the g-band's peak brightness and combine them with public photometric data. This extensive data set robustly reveals a change in the light-curve slope and a possible bump in the rising light curve of a TDE for the first time, which may indicate more than one dominant emission mechanism contributing to the pre-peak light curve. Indeed, we find that the MOSFiT-derived parameters of AT 2019azh, which assume reprocessed accretion as the sole source of emission, are not entirely self-consistent. We further confirm the relation seen in previous TDEs whereby the redder emission peaks later than the bluer emission. The post-peak bolometric light curve of AT 2019azh is better described by an exponential decline than by the canonical t−5/3 (and in fact any) power-law decline. We find a possible mid-infrared excess around the peak optical luminosity, but cannot determine its origin. In addition, we provide the earliest measurements of the Hα emission-line evolution and find no significant time delay between the peak of the V-band light curve and that of the Hα luminosity. These results can be used to constrain future models of TDE line formation and emission mechanisms in general. More pre-peak 1–2 days cadence observations of TDEs are required to determine whether the characteristics observed here are common among TDEs. More importantly, detailed emission models are needed to fully exploit such observations for understanding the emission physics of TDEs.